2010
DOI: 10.1111/j.1469-7610.2010.02217.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional lability in children and adolescents with attention deficit/hyperactivity disorder (ADHD): clinical correlates and familial prevalence

Abstract: EL is a frequent clinical problem in children with ADHD. It is associated with increased severity of ADHD core symptoms, particularly hyperactivity-impulsivity, and more symptoms of comorbid psychopathology, primarily symptoms of oppositional defiant disorder (ODD), but also affective symptoms, and substance abuse. EL in ADHD seems to be more closely related to ODD than to ADHD core symptoms, and is only partly explainable by the severity of ADHD core symptoms and associated psychopathology. Although EL sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
268
4
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(310 citation statements)
references
References 40 publications
26
268
4
12
Order By: Relevance
“…Previous studies (Sobanski et al, 2010;Surman et al, 2013;Vidal et al, 2014) have shown similar results, without differentiating between BD and other axis-1 comorbidities. These two scales therefore seem useful to assess the weight of comorbidities in emotional dysregulation among ADHD sufferers.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies (Sobanski et al, 2010;Surman et al, 2013;Vidal et al, 2014) have shown similar results, without differentiating between BD and other axis-1 comorbidities. These two scales therefore seem useful to assess the weight of comorbidities in emotional dysregulation among ADHD sufferers.…”
Section: Discussionsupporting
confidence: 67%
“…The second strand of research, is linked to a renewed interest in emotional dysregulation (Sobanski et al, 2010) as a clinical feature of ADHD and the overlap between ADHD and paediatric severe mood disorders (Donfrancesco et al, 2011). This has focused interest on amygdala and insula dysfunction in ADHD with recent studies reporting structural (Sasayama et al, 2010) and functional alterations in the amygdala (Brotman et al, 2010;Herrmann et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with previous findings on predominant hyperactive-impulsive subtype (Baeyens et al, 2006;Milich et al, 2001), HI group is characterized by a higher intensity of externalizing symptoms and a lower intensity of internalizing symptoms, except of anxiety depression observed by teachers. As was noted earlier, this subscale seems to be related to mood liability, which was found to be associated with hyperactivity-impulsivity (Sobanski et al, 2010). The IA group is characterized by a low intensity of comorbid symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…It is surprising that symptoms of anxiety-depression were joined in a single component with externalizing symptoms and were not joined with anxiety-withdrawal. Anxiety-depression, as measured by TRF, seems to relate to mood liability, which was found to be associated with hyperactivity-impulsivity (Sobanski et al, 2010). As PCA was conducted in the group characterized by a higher-than-the-population proportion of children with hyperactivity-impulsivity symptoms, these variables were merged together in one component.…”
Section: Discussionmentioning
confidence: 99%